2015
DOI: 10.5455/ijmsph.2015.0310201435
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of oxidative stress in patients of gout and antioxidant effect of allopurinol

Abstract: Background: Various experimental, epidemiological, and clinical studies have shown that hyperuricemia is associated with development of hypertension, visceral obesity, insulin resistance, dyslipidemia, type 2 diabetes, kidney diseases, and cardiovascular and cerebrovascular events. Whether hyperuricemia is a cause or effect is a debatable subject. Although the pathogenesis of these diseases is complex and incompletely understood, it is clear that oxidative stress and damage to proteins and lipids is common for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 17 publications
2
19
1
Order By: Relevance
“…Serum levels of Superoxide dismutase and Glutathione peroxidase were statistically similar for cases and controls. This result differs from that of Chetan et al who found rates of Superoxide dismutase and Glutathione peroxidase significantly lower in subjects with an acute gout attack compared to healthy subjects (p < 0.01) [8]. This difference can be explained by several factors: 1) the status of patients who were newly diagnosed with gout in the study of Chetan and al unlike ours, where 73% of patients had an acute gout attack on chronic gout; 2) the racial differences of our study populations could influence the level of oxidative stress, genetics and eating habits being conditioned by racial origin, they play an important role in the pathogenesis of oxidative stress [9]; 3) when oxidative stress continues, there is a decrease in serum levels of Superoxide dismutase and Glutathione peroxidase which are antioxidants and are the first lines of the body's defense against oxidants.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Serum levels of Superoxide dismutase and Glutathione peroxidase were statistically similar for cases and controls. This result differs from that of Chetan et al who found rates of Superoxide dismutase and Glutathione peroxidase significantly lower in subjects with an acute gout attack compared to healthy subjects (p < 0.01) [8]. This difference can be explained by several factors: 1) the status of patients who were newly diagnosed with gout in the study of Chetan and al unlike ours, where 73% of patients had an acute gout attack on chronic gout; 2) the racial differences of our study populations could influence the level of oxidative stress, genetics and eating habits being conditioned by racial origin, they play an important role in the pathogenesis of oxidative stress [9]; 3) when oxidative stress continues, there is a decrease in serum levels of Superoxide dismutase and Glutathione peroxidase which are antioxidants and are the first lines of the body's defense against oxidants.…”
Section: Discussioncontrasting
confidence: 99%
“…However, malondialdehyde levels were higher among cases compared to controls (p < 0.05). This result is similar to that found by Chetan et al in 2014 [8]. Malondialdehyde is an oxidant, which reflects lipid peroxidation; high levels of Malondialdehyde alone may reflect oxidative damages to lipids in patients with gout who have a metabolic syndrome.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…XO is a significant biological source of free radical generation and allopurinol, as an antioxidant, has direct and indirect antioxidant activity on these free radicals. Furthermore, it can scavenge free radicals such as hydroxyl radical and superoxide anion and numerous studies have shown these effects of allopurinol (5). Oxidative tissue damage after the ischemic diseases such as renal IRI (ischemia/reperfusion injury) is related to the XO and using allopurinol can reduce the renal ischemiainduced oxidative tissue damage (6).…”
Section: Introductionmentioning
confidence: 99%